ANALYSIS THE SUSTAINABILITY OF ORNAMENTAL PLANT BUSINESS IN KENDARI CITY - Malik, Nurhayu; Mappasomba, Musadar; Salahuddin, Salahuddin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to analyze the sustainability of the ornamental plant business in Kendari City. The research sample consists of the entire population of ornamental plant farmers in Kendari City, Southeast Sulawesi Province, Indonesia, totaling 30 people (sampling method: census). The data analysis in this study utilizes descriptive statistics. Descriptive statistics are employed to delineate and characterize the state of the research variables. The results of the study indicate that the sustainability of the Ornamental Plant Business in Kendari City is in the moderate category. The Ornamental Plant Business in Kendari has demonstrated its capacity for sustainability from economic, social, and ecological perspectives. Nevertheless, there is room for enhancement in terms of sustainability from economic and ecological standpoints. From economic and ecological standpoints, sustainability is classified as moderate. Concurrently, sustainability from a social perspective is classified as high priority.